Network Media Player with Built-in Class-D Amplifier - Liska, M.; Štůsek, M. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
The article’s major contributions summarize theory of the design class-D audio amplifier printed circuit board (PCB) with the possibilities of digital or analog input content. It introduces the possibilities of connecting a digital to analog (DA) converter, audio amplifier, analog filtering and digital volume control. Digital input signal is provided via a Raspberry Pi single-board computer, which is wirelessly connected to receive data in the form of streamed content. Furthermore, it describes the regulation of supply voltages for individual active parts of the printed circuit board. It is possible to connect the output of the amplifier to one pair of stereo speakers and one subwoofer speaker. The article contains a general placement of individual components on the PCB.
Keywords: Audio; Amplifier; Filter; Class-D; PCB